Effect of Sales Growth, Profitability and Company Size on Tax Avoidance with Institutional Ownership as Moderating Variable: Pengaruh Sales Growth, Profitabilitas dan Ukuran Perusahaan Terhadap Tax Avoidance dengan Kepemilikan Institusional Sebagai Variabel Moderating - Putri Puji Utami; Herman Ernandi (Academia Open, 2021)
This study aims to examine the effect of sales growth, profitability, and firm size on tax avoidance with institutional ownership as a moderating variable. This study consists of three independent variables, namely sales growth (X1), profitability (X2), and firm size (X3) with the dependent variable being tax avoidance (Y), and the moderating variable, namely institutional ownership (Z). This study uses 20 samples of manufacturing companies in the consumer goods sector during 2017-2019 using the purposive sampling method with data obtained from the annual reports of manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange. The data analysis technique used multiple linear analysis on the SPSS 18 application and moderated regression analysis (MRA). The results of this study are sales growth moderated by institutional ownership has no significant effect on tax avoidance, profitability moderated by institutional ownership has no significant effect on tax avoidance and firm size moderated by institutional ownership has a significant effect on tax avoidance.